Análisis de la aplicación sobre el grillete electrónico y televigilancia para evitar el abuso del control permanente del arresto domiciliario - Mogrovejo Barba, José Alejandro (2022)
It research work called “Analyzing of the application about the electronic fetter televigilance to avoid the abuse of permanent control of the house arrest. “which appear the interest to investigate about the use of the electronic devices of vigilance as an alternative source to the overtaking sanction typified in the article 525 of the Organic integral penal code disposing the home arrested by the decision of the judge, at the same way its control and accomplishment will be in charge of the National Police of obligatory periodical way, accompanied by the electronic devices of video vigilance. The electronic devices of video vigilance were implemented in Ecuador with the finality to find solution of the prison overcrowding which suffers the national penitenciary system affecting severally the state, due to this conflict of the electronic fetter arrived to reduce in a big part the overpopulation prison and be a solid media for the accomplishment of the sanction. In it researched work were applied materials and methods which let the development of the respect researching, at the same way were done interviews and surveys to professionals of law, the results obtained served to propose a legal propose in front of the problem of the electronic devices in its operational, supervision and effectivity provoking the use of the human police resource in a permanent way where a person will accomplish the sanction of a process person in house arrest